C. McGinn. A Religion of Hate / trans. from Engl. V. A. Sergeeva - V. A. Sergeeva (Омский научный вестник: Серия "Общество. История. Современность")
The essay examines universal hate as an alternative foundation to Christianity. According to McGinn, we should hate everyone, even those we love. It is that will enable us to avoid prejudice against individuals and groups who are not part of the inner circle of people for whom we have some sympathy. Hate is justified, natural to human and egalitarian. McGinn does not exclude love from the religion of hate. Emerging love in the background of basic universal hate becomes a more meaningful and valued feeling.